Public Sector Reform, Citizen Engagement, and Development Results in India : Lessons and Frontiers - O'Meally, Simon; Chowdhury, Aheli; Piplani, Varun (World Bank, Washington, DC, 2017)
There is a global consensus that governance and some form of citizen engagement matter for making development more effective, equitable, and sustainable. Yet the devil lies in the details: there is limited agreement on what forms of governance matter most for achieving developmentresults; and there are major gaps in our understanding of how and why different strategies of citizen engagement are successful. Drawing on evidence from India and internationally, this report seeks to move this debate forward. India’s progress in development has been impressive, although it faces several challenges. Its progress, and ongoing challenges, are explained in part by governance dynamics. Moreover, India has been a pioneer in innovative approaches to public sector reform and citizen engagement, ranging from the right to information movement to the widespread implementation of social audits. There are at least three important knowledge gaps in the Indian context. First, the knowledge base is fragmented and patchy, particularly regarding the types of results that citizen engagement might help achieve. Second, our understanding of why certain citizen engagement approaches work and others do not remain partial. Finally, there is room for a deeper debate on the policy and practical lessons that have emerged from India’s rich experience. This report begins addressing these knowledge gaps through a systematic review of available evidence. It analyses 68 well-documented cases of citizen engagement in India, focusing on a subset of citizen engagement initiatives that aim to increase public accountability for development results. In so doing, the report addresses three core questions: what types of results did citizen engagement initiatives contribute to in India? What factors affected whether citizen engagement initiatives in India had an impact and how? And what lessons can be learned from these findings? Given the patchiness of the data, the report does not claim to provide comprehensive or conclusive findings. However, it does identify a range of important trends that could be the focus of further research and policy debate.